A helly number for unions of two boxes in R2 - Marilyn Breen (International Journal of Mathematics and Mathematical Sciences)
Let S be a polygonal region in the plane with edges parallel to the coordinate axes. If every 5 or fewer boundary points of S can be partitioned into sets A and B so that conv A⋃ conv B⫅S, then S is a union of two convex sets, each a rectangle. The number 5 is best possible.